Antiplatelet and Anticoagulation Therapy - Ferro, Albert; Garcia, David A.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Aspirin has been in clinical use for over 100 years, making it one of the oldest commonly used drugs in medicine, and is now predominantly used as an antiplatelet agent. Major new antiplatelet drug classes have recently become available for the clinician that offer the promise of major improvements in the treatment and prevention of arterial thrombotic disease. In the field of anticoagulation, the vitamin K antagonists such as warfarin have not been available for as long as aspirin in the antiplatelet field, and have also had very little in the way of competition until recently; although a number of parenteral anticoagulants have been available, the vitamin K antagonists have been the only orally active anticoagulant drugs. The last few years have seen the arrival of new drug classes, the orally active direct thrombin inhibitors and factor Xa antagonists, which offer a number of advantages, but not without important drawbacks. In the face of these important advances in both antiplatelet and anticoagulant therapy, clinicians often feel confused, even overwhelmed, as to what is now available and which drugs are useful (and indicated) in which circumstances. Antiplatelet and Anticoagulant Therapy is designed with such people in mind. It is written in an easy-to-follow format and with many illustrations to aid clarity and the assimilation of information. Each chapter is written by established authorities in their fields who are also experienced in explaining often complex concepts. The result is a unique book which is not only comprehensive but also clear and useful for the busy medical practitioner.
Antiplatelet agents: current and novel -- Antiplatelet Drug Resistance and Variability in Response: The Role of Antiplatelet Therapy Monitoring -- Anticoagulant Drugs: Current and Novel -- Primary prevention of cardiovascular disease -- Approaches to the Prophylaxis and Treatment of Venous and Cardiac Thromboembolic Disease.
Keywords: Medicine; Cardiology; Medicine & Public Health; Cardiology; Medicine/Public Health, general